Sustainbility in Sharia Invesment - Kurniati Yunus; Erwan Setyanoor; Mansyur, Abdurrahman (Program Studi Ekonomi Syariah, FEBI UIN Datokarama Palu, 2024)
Islamic investments have become the focus of increasing attention in discussions regarding sustainable development as part of efforts to promote more responsible and inclusive economic practices. In this context, this research investigates the link between sustainability and Sharia investment and its implications for sustainable investment practices. Integrating sustainability values into Sharia investment practices has been highlighted as a significant contributor to achieving sustainable development goals. Aligns with the principles of justice, social responsibility, and sustainable environmental management inherent in Sharia. The study also sheds light on various Sharia investment instruments championing sustainable development. With a holistic approach, Sharia investment emerges as a powerful tool for fostering inclusive economic growth, promoting environmental stewardship, and enhancing social welfare.